Improving pancasila education learning outcomes with the CRT approach for grade V students of SDN 2 Prambanan - Sri Suwartini; Putri Zudhah Ferryka; Nela Rofisian; Isna Rahmawati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
The present study examines the improvement in Pancasila learning outcomes of fifth-grade students of SD Negeri 2 Prambanan through the application of the Culturally Responsive Teaching (CRT) approach. The research background was based on the low achievement of student learning outcomes, where as many as 74.6% of them obtained scores below the Learning Objective Completion Criteria (KKTP). This condition was derived from the lack of innovation in the learning process carried out by educators, so that students had difficulty understanding the material. This study used the Classroom Action Research (CAR) type with the Kemmis and McTaggart model, which includes four stages: planning, implementation of action, observation, and reflection. The research subjects were all 28 students of grade V SD Negeri 2 Prambanan, consisting of 16 male and 12 female students. Data collection techniques used included observation sheets, learning outcome tests, and documentation. The data analysis technique used was descriptive analysis with a percentage approach. The research results indicated an increase in learning outcomes in each cycle. In cycle I, 18 students (65.8%) achieved mastery, while in cycle II, this figure increased to 25 students (89.2%). These findings indicate that the Culturally Responsive Teaching (CRT) approach can have a significant positive impact on improving students' Pancasila learning outcomes, particularly in recognising local wisdom.